Fabrication of Ag Nanoparticle-Embedded Covalent Organic Frameworks for Oil Gel with Long-Term Stability and High Lubrication Performance - Zhang, Xiaozhi (Langmuir : the ACS journal of surfaces and colloids, 2024)
In previous reports, covalent organic frameworks (COFs) have demonstrated significant potential as lubricant additives. Herein, we embedded Ag nanoparticles in the DT-COF (polycondensation polymer of 2,5-dihydroxyterephthalaldehyde and 4,4',4″-(1,3,5-triazine-2,4,6-triyl) trianiline) matrix via the ball milling method and utilized this composite (AgDT-COF) as an additive for supermolecule oil gel. The low molecular weight gelator effectively mitigates the dispersion challenges of COFs in lubricant oil, while the embedded Ag nanoparticles enhance the repairing effect and antipressure performance of the lubricant. The resulting Ag@DT-COF gel exhibits a reduction in the average friction coefficient and wear volume of base oil by 46.0% and 87.5%, respectively, and increases the load-carrying capacity to 750 N. The remarkable tribological properties are attributed to the easy adsorption of DT-COF, antiwear characteristic of Ag nanoparticles, and the gelator that ensures the long-term stability of oil gel